THE DISPLAYS OF GENERAL TENDENCIES IN THE AREA OF ITALIAN LANGUAGE CARS TERMINOLOGY - LAVRINCIK, Jan (Journal of Technology and Information Education, 2009)
The study deals with the significance, classification and common linguistic problem in the field of scientific and technical terminology of Italian cars and point of view on education process of common technical subject. A special attention is devoted to system terminological prefix and suffix, it argues about the present use of them with many examples.
Keywords: prefix; suffix; terminology adjective; technical terminology